2010
DOI: 10.1248/bpb.33.1800
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Stabilization of Rat S-Adenosylmethionine Decarboxylase by Putrescine

Abstract: The activity and processing of mammalian S-adenosylmethionine decarboxylase (AdoMetDC) is stimulated by putrescine. To obtain new insights into the mechanism through which putrescine stimulates AdoMetDC, we investigated conformational changes in rat prostate AdoMetDC in the presence or absence of putrescine. We examined the reactivity of purified rat prostate AdoMetDC to the SH-reagent iodoacetic acid (IAA) and its susceptibility to proteolysis in the presence or absence of putrescine using matrix-assisted las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 43 publications
(50 reference statements)
0
6
0
Order By: Relevance
“…Furthermore, the inhibition of polyamine synthesis causes a compensatory increase in SAMDC activity. However, the supply of excess polyamines decreases its activity to nearly zero (Tabor and Tabor, 1984; Heby and Presson 1990b; Wada and Sirahata 2010). Wang et al showed that PUT increased SAMDC activity in IEC-6 cells (Wang et al 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the inhibition of polyamine synthesis causes a compensatory increase in SAMDC activity. However, the supply of excess polyamines decreases its activity to nearly zero (Tabor and Tabor, 1984; Heby and Presson 1990b; Wada and Sirahata 2010). Wang et al showed that PUT increased SAMDC activity in IEC-6 cells (Wang et al 1992).…”
Section: Discussionmentioning
confidence: 99%
“…Spermidine/spermine–N1-Acetyltransferase (SSAT), a highly regulated enzyme plays a crucial role in maintaining polyamine homeostasis (Casero et al 2007; Pegg, 2008; Wada and Shirahata 2010). SSAT acetylates and converts SPM and SPD to SPD and PUT, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both by-products play a role in gastric carcinogenesis through DNA, RNA, protein, and membrane damage caused by reactive oxygen radicals [15]. Polyamine synthesis is stimulated by ODC and AMD [3,4]. ODC is controlled by NQO1 and ornithine decarboxylase antizyme 1 (OAZ1), and polyamines stimulate OAZ1.…”
Section: Discussionmentioning
confidence: 99%
“…Polyamine synthesis is stimulated by ODC, a rate-limiting enzyme, and S-adenosylmethionine decarboxylase (AMD), another key enzyme [3,4], and thus inhibition of ODC and AMD may be of major importance. Previous studies showed that the irreversible inhibition of ODC suppressed cancer formation [5,6].…”
Section: Introductionmentioning
confidence: 99%